2013
DOI: 10.1289/ehp.1206066
|View full text |Cite
|
Sign up to set email alerts
|

AhR-Mediated Effects of Dioxin on Neuronal Acetylcholinesterase Expression in Vitro

Abstract: Background: Deficits in cognitive functioning have been reported in humans exposed to dioxins and dioxin-like compounds. Evidence suggests that dioxins induce cholinergic dysfunction mediated by hypothyroidism. However, little is known about direct effects of dioxins on the cholinergic system.Objectives: We investigated the action of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on acetylcholinesterase (AChE), a key enzyme in cholinergic neurotransmission.Methods: We used SK-N-SH human-derived neuronal cells to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 46 publications
3
46
1
Order By: Relevance
“…In this study, we showed that similar to dioxin (Xie et al 2013), DLCs decreased the enzymatic activity of neuronal AChE in SK-N-SH cells (Fig 1). Based on our previous study and the well-accepted transcriptional action mechanism of dioxin via DRE, we examined the alterations in promoter activity of ACHE upon DLC exposures to further explore the action mechanism.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In this study, we showed that similar to dioxin (Xie et al 2013), DLCs decreased the enzymatic activity of neuronal AChE in SK-N-SH cells (Fig 1). Based on our previous study and the well-accepted transcriptional action mechanism of dioxin via DRE, we examined the alterations in promoter activity of ACHE upon DLC exposures to further explore the action mechanism.…”
Section: Discussionsupporting
confidence: 62%
“…Our previous study has shown that 2,3,7,8-TCDD (10 −10 to 10 −9 M) could decrease AChE enzymatic activity in neurons (Xie et al 2013). Similarly, the present findings showed that exposure to DLCs, including polychlorinated dibenzo-p-dioxins, furans, and polybrominated dibenzo-p-dioxins with TEQs equivalent to 10 −10 to 10 −9 M of 2,3,7,8-TCDD could also reduce the enzymatic activity of AChE (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our previous work demonstrated that dioxin decreased AChE activity by transcriptional suppression of the AChE T subunit, a major variant of AChE transcript in the nervous system, in SK-N-SH human neuroblastoma cells: this suppression was mediated via AhR-dependent pathway [10]. This transcriptional alteration of AChE led to a decrease in the protein expression, which consequently caused the decrease in AChE enzymatic activity [10].…”
Section: Potential Signaling Cascades Beyond Ahr-dependent Pathwaysmentioning
confidence: 99%